Chimpanzee and human midfoot motion during bipedal walking and the evolution of the longitudinal arch of the foot. Issue 104 (March 2017) - Holowka, Nicholas B.; O'Neill, Matthew C.; Thompson, Nathan E.; Demes, Brigitte
Abstract: The longitudinal arch of the human foot is commonly thought to reduce midfoot joint motion to convert the foot into a rigid lever during push off in bipedal walking. In contrast, African apes have been observed to exhibit midfoot dorsiflexion following heel lift during terrestrial locomotion, presumably due to their possession of highly mobile midfoot joints. This assumed dichotomy between human and African ape midfoot mobility has recently been questioned based on indirect assessments of in vivo midfoot motion, such as plantar pressure and cadaver studies; however, direct quantitative analyses of African ape midfoot kinematics during locomotion remain scarce. Here, we used high-speed motion capture to measure three-dimensional foot kinematics in two male chimpanzees and five male humans walking bipedally at similar dimensionless speeds. We analyzed 10 steps per chimpanzee subject and five steps per human subject, and compared ranges of midfoot motion between species over stance phase, as well as within double- and single-limb support periods. Contrary to expectations, humans used a greater average range of midfoot motion than chimpanzees over the full duration of stance. This difference was driven by humans' dramatic plantarflexion and adduction of the midfoot joints during the second double-limb support period, which likely helps the foot generate power during push off. However, chimpanzees did use slightly but significantly more midfoot dorsiflexion than humans in the single limb-support period, during which heel lift begins. These results indicate that both stiffness and mobility are important to longitudinal arch function, and that the human foot evolved to utilize both during push off in bipedal walking. Thus, the presence of human-like midfoot joint morphology in fossil hominins should not be taken as indicating foot rigidity, but may signify the evolution of pedal anatomy conferring enhanced push off mechanics.